2017
DOI: 10.15640/jthm.v5n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Managing Hotels during Economic Challenges: A Case Study on Hotels in Sharm El-Sheikh and Hurghada, Egypt

Abstract: The tourism and hospitality industry in Egypt is suffering since 2011. This study comes to explore the impacts of economic downturn on the basis of hotels and investigate crisis management practices implemented by hotels. This research used questionnaire survey as a research method and sum of 107 forms were distributed on hotels' executives in four and five star hotels in Sharm El-Sheikh and Hurghada, among these 82 forms were valid. The results of the study showed that hotels were much influenced by the econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…As noted by Alonso-Almeida et al 2015, in practice, crisis management is concerned with a mix of reactive and proactive strategies. Radwan (2017) asserts that crisis management remains insufficiently explored and highlights the necessity of further investigations into how to better cope with different crisis situations.…”
Section: Crisis Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…As noted by Alonso-Almeida et al 2015, in practice, crisis management is concerned with a mix of reactive and proactive strategies. Radwan (2017) asserts that crisis management remains insufficiently explored and highlights the necessity of further investigations into how to better cope with different crisis situations.…”
Section: Crisis Managementmentioning
confidence: 99%
“…This is important, because significant reduction of rates during crises could have a destructive impact on the tourism industry after the economic downturn, as it might boosts guests' price sensitivity and lead to price wars among tourism providers. According to Radwan (2017), the branded providers of luxury services should be particularly careful before discounting and lowering the quality of their services, as this practice could influence their image and market position in the long term. Despite the fact that, generally, price reductions present a major threat to tourist firms' and destinations' long-term competitiveness and economic survival Smeral, (2010), Blažević and Drvenkar (2011) reported that during the GFC, Croatian TA lowered the prices of the Adriatic-Sea arrangements by up to 30%.…”
Section: Operational Cmpsmentioning
confidence: 99%
See 3 more Smart Citations